Food grain storage management system - Akila, A; Shalini, P (International Journal of Engineering and Technology, 2018)
Food grain Wastage cripples a countryâ€™s economy to a great extent. Food grain wastage is also associated with wastage of water, manpower during agricultural activities and electricity power used in food processing industries. It even causes deforestation. Adequate measures have to be taken to properly store the food grains so that they remain edible. The proposed storage management system uses the sensors to measure the levels of humidity, temperature and ammonia gas which will help us monitor quality of the food grains. The main idea is to identify the quality of the food grains using the sensors such as Temperature, Humidity and Ammonia Gas. The Quality of the food grain is measured using the factors like Humidity, Temperature and Ammonia gas sensors and sent through Wireless Communication to the server and the server makes the decision and alarms about the quality of the food grain to the maintenance people. Food grain Wastage cripples a countryâ€™s economy to a great extent. Food grain wastage is also associated with wastage of water, manpower during agricultural activities and electricity power used in food processing industries. It even causes deforestation. Adequate measures have to be taken to properly store the food grains so that they remain edible. The proposed storage management system uses the sensors to measure the levels of humidity, temperature and ammonia gas which will help us monitor quality of the food grains. The standard of identifying the food quality could be improved by using more sensors and can be implemented in the Food Storage Industry.Â Â Â